2014
DOI: 10.3389/fimmu.2014.00277
|View full text |Cite
|
Sign up to set email alerts
|

Biased and G Protein-Independent Signaling of Chemokine Receptors

Abstract: Biased signaling or functional selectivity occurs when a 7TM-receptor preferentially activates one of several available pathways. It can be divided into three distinct forms: ligand bias, receptor bias, and tissue or cell bias, where it is mediated by different ligands (on the same receptor), different receptors (with the same ligand), or different tissues or cells (for the same ligand–receptor pair). Most often biased signaling is differentiated into G protein-dependent and β-arrestin-dependent signaling. Yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
168
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(171 citation statements)
references
References 144 publications
(156 reference statements)
1
168
0
2
Order By: Relevance
“…Graphs were derived by combining the mean from each replicate data point (from either 1, 2, or 3 experiments) into one figure. IC 50 values were derived by fitting a curve to each individual experiment and then obtaining the mean and standard deviation from the combined IC 50 values.…”
Section: Hiv Entry Inhibition Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphs were derived by combining the mean from each replicate data point (from either 1, 2, or 3 experiments) into one figure. IC 50 values were derived by fitting a curve to each individual experiment and then obtaining the mean and standard deviation from the combined IC 50 values.…”
Section: Hiv Entry Inhibition Assaysmentioning
confidence: 99%
“…AM3-114 showed dose-dependent but variable binding to all cell lines, except HL-60 where little binding was observed. The variable binding is perhaps a function of the observation that GPCR conformation and tissue/cell type can markedly affect ligand binding and activity (49,50).…”
Section: I-bodies Bind Cancer Cell Lines and Inhibit Cell-mediatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the majority of chemokines are able to bind to several chemokine receptors, and receptors can often be activated by various ligands, leading to the hypothesis that the inhibition of one single chemokine or receptor is not sufficient to observe beneficial clinical effects. However, data are currently accumulating to demonstrate that the chemokine system is not redundant in terms of signal cascades as well as in the temporal and spatial patterns of expression in vivo (24). Recently it has been shown that the ligands for CXCR3 induce different effects.…”
mentioning
confidence: 99%
“…Maciejewski-Lenoir et al [111] Steen et al [112] made the promiscuity of chemokine receptors for several peptide ligands responsible for the difficulties to develop effective small-molecule therapeutics targeting chemokine receptors. With regard to only one endogenous ligand, the CX3CR1 receptor provides better prerequisites than the most other chemokine receptors.…”
Section: Cx3cr1 Chemokine Receptormentioning
confidence: 99%